Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fpsyg.2018.01134
|View full text |Cite
|
Sign up to set email alerts
|

Boost Me: Prevalence and Reasons for the Use of Stimulant Containing Pre Workout Supplements Among Fitness Studio Visitors in Mainz (Germany)

Abstract: The rapidly increasing interest in fitness related sports over the past few years has been accompanied by a booming industry of nutritional supplements. Many of these substances have unproven benefits and are even potentially harmful to the user. The aim of this study was to determine the prevalence and reasons for nutritional supplement (NS) use among fitness studio visitors in Mainz (Germany), emphasizing new multi-ingredient based supplements such as pre workout boosters (PWBs). Some of the PWBs contain sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 53 publications
(108 reference statements)
0
17
0
Order By: Relevance
“…Interestingly, a small percentage of MIPS users reported that banned stimulants and anabolic agents were also a desired ingredient when selecting MIPS products. This preference has been reported previously, as a recent survey of German fitness studio visitors [25] found that 20% of the pre-workout users listed 1,3-dimethylamylamine (DMAA), a synthetic stimulant that is banned in the United States, as a desired ingredient for its stimulatory benefits. Improving performance tends to be a common reason for dietary supplement use among regular exercisers and athletes, with correcting nutritional deficiencies and health benefits as secondary outcomes [26,27,28].…”
Section: Discussionmentioning
confidence: 56%
“…Interestingly, a small percentage of MIPS users reported that banned stimulants and anabolic agents were also a desired ingredient when selecting MIPS products. This preference has been reported previously, as a recent survey of German fitness studio visitors [25] found that 20% of the pre-workout users listed 1,3-dimethylamylamine (DMAA), a synthetic stimulant that is banned in the United States, as a desired ingredient for its stimulatory benefits. Improving performance tends to be a common reason for dietary supplement use among regular exercisers and athletes, with correcting nutritional deficiencies and health benefits as secondary outcomes [26,27,28].…”
Section: Discussionmentioning
confidence: 56%
“…Of the participants in the present study that reported using supplements, 44% reported the use of pre-workout formulas, mainly to stimulate the motivation to work out and increase energy levels. This prevalence rate is considerably higher when compared to German regular gym users (12%) [ 45 ]. The reported prevalence reported in the present study can be considered worrying, as pre-workout formulas are associated with side-effects (dizziness and nausea) and adverse events, such as heart rhythm abnormalities [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that approximately 30% of high school football athletes reported consuming pre-workout supplements. In a previous study on the topic, 25.8% of fitness studio visitors in Mainz, Germany were reported to use a “pre-workout booster.” 12 A different study in college student athletes reported that 86% took a form of pre-workout supplements. 6 The large difference in results between our study and that study may be due to the study populations or the definition of pre-workout supplements.…”
Section: Discussionmentioning
confidence: 99%